Novel Nanocrystal Injection of Insoluble Drug Anlotinib and Its Antitumor Effects on Hepatocellular Carcinoma - Luo, Mei; Sun, Huiwei; Jiang, Qiyu; Chai, Yantao; Li, Congshu; Yang, Bin; Hong, Zhixian (Frontiers in Oncology, 2021)
The molecularly targeted agent anlotinib offers a novel therapeutic strategy against advanced hepatocellular carcinoma (HCC). With this study, we aimed to solve the technical problem of anlotinib being insoluble in injectable solutions; we also aimed to assess the antitumor activity of anlotinib on hepatocellular carcinoma cells. We prepared an anlotinib nanocrystal injection by wet grinding, and we optimized the prescription process using a transmission electron microscope (TEM) and a laser particle size analyzer (LPSA). The release of anlotinib from the injected nanocrystals was evaluated using LC-MS/MS in vitro, and the drug’s anti-tumor effects were assessed in a nude mice tumor model. The anlotinib nanocrystals had a uniform particle size distribution (the average nanoparticle size was ~200 nm). The preparation of anlotinib into nanocrystals did not change the original crystal structure. The intravenous injection of anlotinib nanocrystals achieved anti-tumor activity at very low doses compared to those required for oral administration of an anlotinib suspension: anlotinib nanocrystals at a dose of 50 μg/kg inhibited the subcutaneous growth of the HCC cell line MHCC97-H; whereas the dose of anlotinib suspension required for an equivalent effect was 1 mg/kg. Therefore, our novel anlotinib nanocrystal injection preparation provides an option for achieving a safe and effective molecularly targeted therapy against advanced HCC.